Perfectly imperfect: Embracing sub-optimal vegetables in Coimbatore farmer’s market - Sathya, K N; Uma, K; Malarkodi, M (Plant Science Today, 2025)
India is one of the largest producers of vegetables globally, consistently ranking among the top countries in terms of production. However, post-harvest losses continue to be a major problem in the food sector because of poor handling, storage and transportation. Despite these losses, customers frequently ignore vegetables that are not at their best but still have nutritional value due to their aesthetic flaws. This is because consumers and retailers have high expectations in purchasing vegetables. The study explores factors that influence purchasing behavior and consumer preferences in sub-optimal vegetables. Using a well-structured questionnaire data was collected from 250 respondents in Coimbatore farmers market and analyzed by using factor and conjoint analysis. A total of four factors such as buying expectations, attitudes, benefits and price were identified on purchasing behaviour of sub-optimal vegetables. Combination of fresh, firm, without spots with a price discount of 50-75 % has a higher utility score and it is a highly preferred attribute of the consumer in buying sub-optimal vegetables. This study contributing to food waste reduction and supporting sustainable practices.